THE IMPLEMENTATION OF USING ABACUS MEDIA TO ENHANCE MATHEMATICS SKILLS AND INTEREST IN FIRST GRADE ELEMENTARY STUDENTS OF SDN 060857 MEDAN TEMBUNG - Puspita, Rindi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
The objective of this study is to determine the implementation of using abacus in Mathematics especially in addition and subtraction at first grade elementary school. This research used Classroom Action Research that had 2 cycles and the researchers also made a pre-test before conducting the cycles. The subject of this research is the subject of this research is the first grade students of Medan Tembung state 060857 elementary school totaling 24 students. The results of this research found 22 (91.66%) students had reached the level of learning completeness, while 2 people (8.33%) had not reached the level of learning completeness, but the average was improving. The average was 82.5.